1983
DOI: 10.1002/pol.1983.170211003
|View full text |Cite
|
Sign up to set email alerts
|

Curing epoxy resins with anhydrides. Model reactions and reaction mechanism

Abstract: The mechanism of acid curing of epoxy resins catalyzed with tertiary amines was investigated by using model systems composed of phenylglycidyl ether and benzoic acid or acetic acid anhydrides in the presence of benzyldimethylamine. The reaction was studied by NMR spectrometry, liquid chromatography, and ozone absorption. The main findings are that (1) the tert‐amine is bound chemically and irreversibly during the reaction under the formation of a quaternary ammonium salt magnified image and (2) 1‐phenyloxyprop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(90 citation statements)
references
References 8 publications
2
87
0
1
Order By: Relevance
“…This alternating anionic copolymerization controls propagation of the polymer chain. The mechanism for this major channel was first proposed by Matejka et al 14) and most recently refined by Leukel et al 15) Trappe et al 16) found that the initiation rate is significantly slower than the rate of propagation. Assuming that the initial stages of epoxy-anhydride cure are controlled by initiation, we may assign the value of L 20 kJ N mol -1 to the activation energy of initiation.…”
Section: Resultsmentioning
confidence: 98%
“…This alternating anionic copolymerization controls propagation of the polymer chain. The mechanism for this major channel was first proposed by Matejka et al 14) and most recently refined by Leukel et al 15) Trappe et al 16) found that the initiation rate is significantly slower than the rate of propagation. Assuming that the initial stages of epoxy-anhydride cure are controlled by initiation, we may assign the value of L 20 kJ N mol -1 to the activation energy of initiation.…”
Section: Resultsmentioning
confidence: 98%
“…1 Propagation occurs through the alternating addition of epoxy and anhydride functionalities to the growing chain. But as active epoxides (alkoxides) at chain ends react at a faster rate than active anhydrides (carboxylates), 2,3 an almost simultaneous addition of an epoxy/anhydride couple to the growing chain takes place. Therefore, the propagation step may be described by a single rate constant.…”
Section: Introductionmentioning
confidence: 99%
“…O mecanismo de polimerização epóxi-anidrido na presença de uma de amina terciária como catalisador é bastante complexo, mas a maioria dos autores concorda que o mecanismo de reação é aniônico (Figura 2) [30] . Pode-se dizer que a reação é iniciada pela reação entre a amina terciária com o grupo epóxi formando um "zwitterion" que apresenta em sua estrutura um átomo de carbono quaternário e um anion alcóxido (reação 1) e que o processo de propagação ocorre através de uma acilação seguida de uma esterificação (reação 2 e 3).…”
Section: Figuraunclassified